Alfabetização e letramento na EJA: buscando articulações com o conhecimento científico - SANTOS, Thaís Priscila Bahia dos (2020)
The present experimental work has as a report some results of research carried out in a group of Youth and Adult Education (EJA), in which aspects involved in the development of activities of grammar of the mother tongue integrated to the knowledge of sciences are analyzed. During the development of the activities it was possible to perceive that the work with socially significant themes positively favored the insertion of the scientific knowledge in the EJA and the participation of the students. Scientific literacy can be used as a way to enhance the teaching of the mother tongue, and for this we perceive the work with the textual gender as a way of interconnecting the contents of different areas of knowledge.